Strategic complexities and opportunities in Welsh youth justice: exploring YJB Cymru - Stephen Case (2014)
Purpose The paper presents and discusses the findings of a Strategic Insight Programme placement that explored the Youth Justice Board for Wales (YJB Cymru), a division of the YJB for England and Wales since the abolition of the regional structure in April 2012. The focus of the placement was on exploring the role of YJB Cymru in the development of youth justice policy and practice in the unique, partially devolved context of Wales. The paper aims to discuss these issues. Design/methodology/approach The research was conducted over a six-month period from February to July 2013. A multiple methods design was adopted, consisting of semi-structured interviews with key stakeholders (YJB Cymru staff, Welsh Government staff and Youth Offending Team staff), observations of policy and practice mechanisms (YJB Cymru meetings, YOT projects) and documentary analysis of YJB Cymru publications. Findings Thematic analyses demonstrated that YJB Cymru has an increasingly important role in policy and practice development structures and processes in England and Wales more broadly (e.g. within the YJB for England and Wales) and in the Welsh national context specifically. YJB Cymru fulfills a role of dual influence – working both with government (UK and Welsh) and youth justice practitioners (mainly YOT managers and staff) to mediate and manage youth justice tensions in the partially devolved Welsh policy context through relationships of reflective and critical engagement. Originality/value This study draws inspiration from the groundbreaking research of Souhami (2011) and builds on those findings to provide a unique insight into the organisation and role YJB Cymru in the complex and dynamic context of youth justice in Wales.